1955
DOI: 10.1071/bi9550068
|View full text |Cite
|
Sign up to set email alerts
|

Strains of Myzus Persicae (sulz.) Active and Inactive with Respect to Virus Transmission

Abstract: The inconsistent transmission of a persistent yellows virus disease of spinach by its vector, Myztls persicae, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1958
1958
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…That insect vectors vary within species in ability to transmit plant viruses is now well documented with examples existing for aphid vectors of non-persistent, semipersistent and persistent plant viruses and leafhopper vectors of persistent viruses (Storey, 1932;Storey & Ryland, 1955;Stubbs, 1955;Bj6rling & Ossiannilsson, 1958;Rochow, 1963;Sohi & Swenson, 1964;Hinz, 1966;Bath & Chapman, 1967;Tsai et al, 1972;Thottappilly et al, 1972). In addition, forms and stages of aphid j vectors have been shown to vary significantly in efficiency of non-persistent and persistent virus transmission (Anderson, 1951;Swenson, 1962;Ehrhardt & Schmutterer, 1965;Chapman & Bath, 1968;Thottappilly, 1969Thottappilly, , 1971).…”
Section: Discussionmentioning
confidence: 99%
“…That insect vectors vary within species in ability to transmit plant viruses is now well documented with examples existing for aphid vectors of non-persistent, semipersistent and persistent plant viruses and leafhopper vectors of persistent viruses (Storey, 1932;Storey & Ryland, 1955;Stubbs, 1955;Bj6rling & Ossiannilsson, 1958;Rochow, 1963;Sohi & Swenson, 1964;Hinz, 1966;Bath & Chapman, 1967;Tsai et al, 1972;Thottappilly et al, 1972). In addition, forms and stages of aphid j vectors have been shown to vary significantly in efficiency of non-persistent and persistent virus transmission (Anderson, 1951;Swenson, 1962;Ehrhardt & Schmutterer, 1965;Chapman & Bath, 1968;Thottappilly, 1969Thottappilly, , 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of honeydew are produced which lead to heavy growth of sooty moulds and inhibition of photosynthesis. M. persicae is reported to transmit more than 100 virus diseases worldwide and a number of these occur in Australia (Stubbs 1955;Kennedy et al 1962). For example, on lupins in Western Australia, it transmits cucumber mosaic virus in a non-persistent manner.…”
Section: Pest Statusmentioning
confidence: 99%
“…It is a well established fact that virus-vector studies with a mixed population of a particular species might introduce variations in the transmission studies. Much work has been done to determine individual efficiency cif aphids in transmitting circulative viruses (STUBBS 1955, BJORLING and OSSIANNILSSON 1958, SAKSENA, SINGH and SILL 1964, ROCHOW and EASTOP 1966, BATH and GHAPMAN 1966 but there are very few records regarding stylet borne viruses. BAWDEN and KASSANIS (1947) reported wide differences in the efficiency of a number of aphid species in transmission of potato virus Y and suggested that the low efficiency of some species might be due to the relatively few active individuals in these species.…”
Section: Introduction I Jmentioning
confidence: 99%